2018
DOI: 10.7554/elife.33761
|View full text |Cite
|
Sign up to set email alerts
|

Covalent linkage of the DNA repair template to the CRISPR-Cas9 nuclease enhances homology-directed repair

Abstract: The CRISPR-Cas9 targeted nuclease technology allows the insertion of genetic modifications with single base-pair precision. The preference of mammalian cells to repair Cas9-induced DNA double-strand breaks via error-prone end-joining pathways rather than via homology-directed repair mechanisms, however, leads to relatively low rates of precise editing from donor DNA. Here we show that spatial and temporal co-localization of the donor template and Cas9 via covalent linkage increases the correction rates up to 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 35 publications
1
114
1
Order By: Relevance
“…While these studies were underway, reports of genetic fusions of Cas9 to avidin, SNAP tag, or porcine circovirus 2 protein (PCV), which can also bind to donor DNAs, appeared in the literature, [43][44][45][46] and our studies complement these approaches in multiple ways. First, at 17-nt, our Cas9-adaptor constructs are much smaller than the reported constructs, with the possibility of reducing this to as low as 13 nt.…”
Section: Discussionmentioning
confidence: 85%
“…While these studies were underway, reports of genetic fusions of Cas9 to avidin, SNAP tag, or porcine circovirus 2 protein (PCV), which can also bind to donor DNAs, appeared in the literature, [43][44][45][46] and our studies complement these approaches in multiple ways. First, at 17-nt, our Cas9-adaptor constructs are much smaller than the reported constructs, with the possibility of reducing this to as low as 13 nt.…”
Section: Discussionmentioning
confidence: 85%
“…3G). We also tested the hypothesis that biotinylating Cas9 and adding a streptavidin tag to the biotinylating ssODN to physically link the CRISPR-Cas9 complex to the repair oligo would increase rates of HDR, as has been previously suggested (50). Despite clear Cas9 biotinylation, we found that this strategy unexpectedly abolished Cas9 activity (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, it has been reported that covalently linking an ssDNA repair template to Cas9 (Fig. 3G) increased HDR frequency by up to 30 times in multiple cell lines (Aird et al, 2018;Savic et al, 2018). An alternative attachment method for dsDNA could include adding a site-specific DNA-binding domain to Cas9 and including its binding site at the end of the dsDNA repair template (Fig.…”
Section: Thousands Of Birdsmentioning
confidence: 89%